If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 5x + -3x + 4 = 3x Reorder the terms: 4 + 2x + 5x + -3x = 3x Combine like terms: 2x + 5x = 7x 4 + 7x + -3x = 3x Combine like terms: 7x + -3x = 4x 4 + 4x = 3x Solving 4 + 4x = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 4 + 4x + -3x = 3x + -3x Combine like terms: 4x + -3x = 1x 4 + 1x = 3x + -3x Combine like terms: 3x + -3x = 0 4 + 1x = 0 Add '-4' to each side of the equation. 4 + -4 + 1x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 1x = 0 + -4 1x = 0 + -4 Combine like terms: 0 + -4 = -4 1x = -4 Divide each side by '1'. x = -4 Simplifying x = -4
| 7y^2+13y-2=0 | | =2x^2+16x-2 | | 4x^2-21x-49=0 | | 4x+5+2x=7x | | 4x-21x-49=0 | | .25(x-8)=6 | | 13-3x=-6x+16 | | 5y-1+5y=4 | | 255=(-2x)(.147-x)(.18-x) | | 2x+3x=32 | | 3x^2-67x=-6x^2-5x-48 | | =-2x^2-28x-96 | | 3x^2-10x+25=0 | | -4m+8=-3m+1 | | .5(x-6)=4 | | X^3-64y^3= | | 4*x^3-12*x^2+10*x-8=0 | | 2a^2+7a-9= | | 5+.25n-1.25n=n | | 32+3x(x-4)=8x-40 | | 5x-13=6x-7 | | x-7.4=-5.8 | | x+7=4(5x-6) | | -a/4=-15 | | 5x^2-21z+4=0 | | Y-4=-15 | | .03g-(2g+3)=1.8 | | ln(6x+21)=ln(2x+1) | | 2x-320=8(x-8) | | 20+320=8(x-8) | | -2x+55=7x+19 | | 15m=63 |